Analisis Perbandingan Metode Quenched Terhadap Sifat Mekanik Baja Tahan Karat Austenitik Berbasis Big Data - Leni, Desmarita; ., Islahuddin; ., Mulyadi; ., Hendra; Sumiati, Ruzita (Rekayasa Material, Manufaktur dan Energi, 2024)
A profound understanding of the mechanical properties of stainless steel is crucial in modern industrial applications. However, comprehensively understanding the mechanical properties of stainless steel requires sufficient testing to gather data on its characteristics. In this research, an analysis was conducted on the influence of chemical composition and heat treatment on the mechanical properties of stainless steel, utilizing data from the Material Algorithm Project (MAP), which is a material database. The dataset comprises 986 samples, encompassing 11 chemical elements, variations in quenching, and 3 mechanical properties of stainless steel. The data was analyzed using descriptive statistics and Pearson correlation to examine the relationships between these variables. The research results indicate a negative correlation of -0.35 between temperature and Yield Strength (YS) in samples of steel undergoing air cooling. The YS values in this treatment can reach 300 MPa at temperature combinations ranging from 1300 K to 1330 K, with heating times ranging from 180 seconds to 420 seconds. Meanwhile, water cooling exhibits a wide range of cooling times and relatively high temperatures. Combinations of time between 1400 seconds and 2200 seconds and temperatures between 1300 K and 1400 K result in YS ranging from 240 MPa to 260 MPa. This research suggests that experimental material testing datasets not only play a passive role in validating an experiment but can also be actively utilized in the analysis and design of materials more effectively.